Fundamental Rights and Freedoms of Citizen-Employee in Labour Law - Ali Güzel; Deniz Ugan Çatalkaya; Hande Heper (Annales de la Faculté de Droit d’Istanbul)
Since the 1980s, fundamental rights and freedoms have not only appeared and taken on a particular dimension within employment but also started covering all aspects of citizen employees’ private and professional lives. The appearance of citizen employees’ fundamental rights and freedoms basically indicate the contemporary evolution of labour law. Due to this development, employer actions that restrict employees’ fundamental freedoms have formed the essence of labour disputes. For this reason, not only have new rights with varied functions made their appearance in labour law; at the same time, a specific method has arisen in judicial reasoning around a general principle enshrined in both national and international legislation. This study approaches the subject of the protection of citizen employees’ fundamental rights and freedoms in three sections. The first section evaluates the historical overview of these rights and freedoms, their inevitable progress, and their essential function in labour law. The second section examines some examples of fundamental employee rights inlight of doctrine and case law. Given that fundamental employee rights and freedoms arose to limit the power of employers, the third and final section is devoted to the reconciliation of power and freedoms within the workplace through the method of legal control based on the principle of proportionality.